Penggunaan Microsoft Exccel dalam Penyusunan Laporan Keuangan - Chairul Nazar Saing; Nurwani Nasution; Silvia Br Nainggolan; Sovy Muti Ardianty Hsb; Nurbaiti Nurbaiti (Universitas Muhammadiyah Enrekang, 2022)
In this article, the author describes the applications needed for solving calculation problems effectively, quickly and accurately using Microsoft Excel software and makes this article intended to help readers understand this application properly and correctly. The function of ICT (Information and Communication Technology) is needed by students as a means to deal with the changes and demands of the times in the era of the Industrial Revolution 4.0. Operating a computer is part of a hard skill, we must have the skills to operate programs in Windows and the most commonly used program is Microsoft Excel. Microsoft Excel is one of the many application programs in the Microsoft Office office application package dedicated to processing numbers (grouped data) or also known as a sheet application program that automatically processes data such as calculations, formulas, using functions, tables, charts, and management. Data to make data information is used to make decisions.